Green Building Perception Matrix, A Theoretical Framework - Mansour, Osama E.; Radford, Scott K. (Proceedings of the Annual Architectural Research Symposium in Finland, 2014)
Research has consistently shown that architects differ from the public in what they prefer in buildings. Today, as building design and construction evolve to more sustainability, some recent studies show that the overall level of satisfaction of occupants of green buildings still does not exceed the level of satisfaction in conventional structures. Satisfaction is typically measured, with Post Occupancy Evaluation, which gathers feedback from building occupants about aspects such as comfort, indoor air quality, and aesthetics. This raises some questions: Do people perceive green building design as consistent with their desire for sustainability? Do ratings of green buildings by systems such as LEED or BREAM affect the level of satisfaction of laypeople? Can owners and occupants of green buildings be considered as green consumers, who are attracted to green products because of their willingness to mitigate the impact of human activities on the environment? This article examines Peattie’s (2001) green purchase perception matrix as a means of understanding occupants’ perceptions of green-labeled buildings. An analytical approach has been taken to identify the influential factors, which are involved in this relationship. As a result, the authors propose a green building perception matrix that addresses the compromise that occupants must make in green buildings and the confidence that building systems are indeed making a difference environmentally. Understanding and using this matrix may help green building designers to improve the level of satisfaction of building’s owners and occupants. The discussion is critical for future research on how green building design attributes can be used as a catalyst for green consumption behavior.